Aerobic Bacterial Resistance In Diabetic Foot Ulcer From Chennai - ARUMUGAM SURESH,; GOPAL MUTHU,; RAMESH SRIVANI,; ANAND MOSES, (International Journal of Pharma and Bio Sciences, 2011)
Fifteen percent of all diabetics develop a foot ulcer at some point in their lives that is highly susceptible to infection and that spreads quite rapidly, leading to overwhelming tissue destruction and subsequent amputation. Wound specimens were collected and processed from patients attending diabetic foot clinic tertiary care Hospital isolates were characterized and antimicrobial susceptibility testing performed by standard protocols. Out of 123 patients analyzed the age group between 25-75 years with an average of 55.52 ± 11.64. 171 isolates were obtained wound specimens were grouped in to different Wagner grading, gram-positive organisms were 66/171 and grams negative were 97/171. The salient features of the present study are Gram-negative isolates are predominant from wound specimens. Linezolid and Vancomycin found to be highly sensitive to the group especially gram-positive isolates. In gram negative Ciprofloxacin and Tobramycin found better sensitivity and ceftazidime showed higher percentage of resistance by MIC.